Addressing The Customers: The Influence Of Status, Physical Contact, And Age On Customers' Level Of Irritation (Malaysian Management Journal, 1995)
How do customers react when they are called by their first name in a service encounter? This paper explores the influence of a service provider's status, physical contact and age on customers' feelings of irritation when they are first-named by a service provider. Data for the study was a sample of ITM students. From three replications of the study, mixed support was obtained for the influence of status and physical contact, while age registered a non-significant influence on customers' level of irritation. Some interactions between the independent variables were also discovered.